THE EFFECTIVENESS OF PANDAN LEAVES BOILD ON THE PAIN LEVEL OF PATIENTS WITH HERNIA NUCLEUS PULPOSUS (HNP) DISEASE AT POLYCLINIC OF PMC HOSPITAL - dwi elka fitri; Fitra Wahyuni; Selfi Elva Yenti (LPPM Universitas Abdurrab, 2025)
Background: Hernia Nucleus Pulposus (HNP) suffered by most mature and elderly women in Indonesia. One effect of this disease is physical mobility disorder due to recurring pain. The average of HNP patient depends on he chemical analgesic drugs, which are feared impacting other organs when it consumes every day. Pandan leave is one easy loacal indonesian plants to find and own the analgetic effect to help reduce the pain. Methods: This research was a Quasy Experimental Research using The non-equivalent group design. The sample of this research in amount of 30 people, using purposive sampling technique. In implementing this research, pre-test and post-test were conducted to measure the level of pain by the respondent before and after the treatment, then intervention of pandan leaves decoction were given 1x a day and given in 3 days in experimental group, then in control group to reduce the pain researcher train them the deep breath technique and imagery guidance. Analysis test comparing the average pain level using Wilcoxon and Mann-Whitney. Results: The result of this study obtained Pvalue of experimental group are : 0,001, and Pvalue of control group are: 0,18. Then man-whitney test were conducted and obtained pvalue: 0,0001. Conclusion: From the result of this research, it can be concluded that pandan leaves decoction is effective in reducing the pain of HNP patient. With this study, it is hoped that the nurses in community can socialize this pandan leaves decoction to HNP patient.